2011
DOI: 10.1016/j.jaci.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural and immunologic cross-reactivity among filarial and mite tropomyosin: Implications for the hygiene hypothesis

Abstract: Background-The "Hygiene Hypothesis" suggests that parasitic infection modulates host immune responses and decreases atopy. Other data suggest parasitic infections may induce allergic responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 48 publications
1
72
0
7
Order By: Relevance
“…Perhaps cross-reactivity between helminth proteins and dust mite, for example, plays a role in the pathogenesis of parasitic infection and allergic sensitization [49]. Santiago et al [49] demonstrated almost 72% homology between filarial and dust mite tropomysins. However, Sangsupawanich et al [50] reports from his cohort that hook worm and mite allergen were independently associated with childhood wheeze.…”
Section: Varicella Tuberculosis and Parasitesmentioning
confidence: 99%
“…Perhaps cross-reactivity between helminth proteins and dust mite, for example, plays a role in the pathogenesis of parasitic infection and allergic sensitization [49]. Santiago et al [49] demonstrated almost 72% homology between filarial and dust mite tropomysins. However, Sangsupawanich et al [50] reports from his cohort that hook worm and mite allergen were independently associated with childhood wheeze.…”
Section: Varicella Tuberculosis and Parasitesmentioning
confidence: 99%
“…Depletion ELISAs were performed as previously described (27,28). Briefly, flat-bottom plates (CoStar, USA) were coated overnight at 37°C with 10 g/well of peptide 1 (EEDESKKKSCGDEGEPKVE), peptide 2 (VTEGGEDKKK), and peptide 3 (EVAEAPPAEAAPA) and then washed and blocked as described above.…”
Section: Methodsmentioning
confidence: 99%
“…[116][117][118][119][120][121][122][123][124][125][126][127][128] We have demonstrated that helminth infection can be associated with increased IgE responses to many different allergens, especially those structurally related to parasite antigens. 116 Individuals infected with filarial parasites were shown to have higher levels of IgE against HDM and cockroach extracts (that have several major allergens with homologues in filarial parasites) but not against timothy grass extract, an allergen extract with just a few minor allergen homologues in helminths.…”
Section: -89mentioning
confidence: 99%
“…116 Individuals infected with filarial parasites were shown to have higher levels of IgE against HDM and cockroach extracts (that have several major allergens with homologues in filarial parasites) but not against timothy grass extract, an allergen extract with just a few minor allergen homologues in helminths. 116 In more detailed studies, cross-reactivity among allergens and parasite molecules has been well described for tropomyosin, 120,122,129 considered a pan-allergen. 130 Tropomyosins are highly conserved across many species and cross-reactivity is not surprising from the structural point-of-view.…”
Section: -89mentioning
confidence: 99%